Arabic Language Development Program at Islamic Boarding Schools in Sidoarjo Regency - Zakiyyatul Aini; Doni Septi (Universitas Muhammadiyah Sidoarjo, 2023)
By looking at the students who often communicate in javanese and less applying linguistics they can make less maximum. With the reality that exists in Islamic boarding school, it shows that there are several factors. In an institution requires effort and programs development of good Arabic so that students, and students can develop skills in Arabic. The research is a qualitative research where the data researchers get will be explained descriptively, and the methode used ai by wat of observation, interviews and documentation. The results of the study show (1) the language development program there are a lot of Arabs at the Annur Sidoarjo Muhammadiyah Islamic Boarding School improve students&rsquo language skills (2) The inhibiting factor is the teacher less competent, less supportive environmet, less time and facilities infrastructure is still lacking (3) Sipporting factors ustadz- ustadzah ISMUBA graduates from well known boarding school snd universities, there are organitation from student (IPM) and different subjects support.